IMPROVING THE COUNTRY'S MANAGEMENT SYSTEM AND ENSURING THEIR EFFECTIVENESS - Uktamov Khusniddin (Scholar Express Journals, 2024)
This article discusses the crucial role of effective management in spurring economic growth in developing countries. Good management is the basis for designing, implementing and optimizing economic policies that support the development of key sectors, factors such as operationally efficient human resource management, innovation and stability. proven to be a key driver in achieving sustainable growth through case study analysis and literature review. This article outlines the positive impact of effective management on company productivity and national economic growth
Keywords: management; positive; economic